Costs and resource needs for primary health care in Ethiopia: evidence to inform planning and budgeting for universal health coverage - Alebachew, Abebe; Abdella, Engida; Abera, Samuel; Dessie, Ermias; Mesele, Tesfaye; Mitiku, Workie; Muñoz, Rodrigo; Opuni, Marjorie; Teplitskaya, Lyubov; Walker, Damian G.; Gilmartin, Colin (Frontiers in Public Health, 2023)
The Government of Ethiopia (GoE) has made significant progress in expanding access to primary health care (PHC) over the past 15 years. However, achieving national PHC targets for universal health coverage will require a significant increase in PHC financing. The purpose of this study was to generate cost evidence and provide recommendations to improve PHC efficiency. We used the open access Primary Health Care Costing, Analysis, and Planning (PHC-CAP) Tool to estimate actual and normative recurrent PHC costs in nine Ethiopian regions. The findings on actual costs were based on primary data collected in 2018/19 from a sample of 20 health posts, 25 health centers, and 8 primary hospitals. Three different extrapolation methods were used to estimate actual costs in the nine sampled regions. Normative costs were calculated based on standard treatment protocols (STPs), the population in need of the PHC services included in the Essential Health Services Package (EHSP) as per the targets outlined in the Health Sector Transformation Plan II (HSTP II), and the associated costs. PHC resource gaps were estimated by comparing actual cost estimates to normative costs. On average, the total cost of PHC in the sampled facilities was US 11,532